“Almowashah at Ibn Zaydoun: prosody and formal study” (Albayan Scientific Journal, 2023)
This search tried to study almowashah of Ibn Zaydoun from a formal and prosody perspective. And compare it with what Ibn Sanaa Elmolk founded in his book (darattiraz) about this perspective.Ibn Zaydoun had only two mowashah have been studied from its prosody level through a descriptive and inductive approach; the thing which help in knowing the prosody and formal structure of Ibn Zaydoun’s mowashah.Finally, this search concluded a lot of very important results about Ibn Zaydoun’s mowashah, specified in this two components:• Adopting a prosody system of the poetry basically.• Infraction of the almowashah’s formal system.